Profit and Profitability – Analysing the Main Business of an Industrial Enterprise - Chukov, Krastyo (Research Papers, 2009)
The paper outlines the techniques of analyzing profit and profitability of the main business of an industrial enterprise.The study is an attempt to present the methodology for analyzing the profit of the products’ sales as a logical sequence. Based on a critical analysis, the author argues an approach aimed at distinguishing the influence of the changes in the bulk of the output and the structure of the range of the products. Three factors are isolated to ensure the accountability of information – the breakdown of the costs of the articles sold - costs of the main business, sales costs and overheads. As a whole, the methodology allows to determine and assess the influence of the direct factors on the divergence between the actual profit and the profit margin measure.It is claimed that in conformity with the economic logic it is justifiable to base the analysis of the sales profitability on the findings of the indicator “Complete costs per 100 BGL output”. With a view of meeting the objectives and goals of the analysis the latter indicator may be analyzed in different aspects which relate to different classifications of the costs making up the prime cost of the goods sold.On the basis of the critical analysis the paper develops a methodology for analyzing the assets required for the main business. The author argues the need and the possibility for an in-depth analytical assessment of the profitability of industrial assets from the viewpoint of the three factors – changes in the load factor of the long-term tangible assets, changes in the employment factor of the short-term assets, and changes in the profitability of the sales. Accordingly, the paper proposes an improved and expanded Dupont’s model for a deterministic factor analysis of the profitability of industrial assets. The paper includes a case study as a concrete example. The statistics used in the paper are approximate.